Analysing the sustainability of procurement in family businesses: A study of measurable investments and practices based on ESG principles - Philipp Schmidt (Junior Management Science (JUMS), 2024)
Sustainability has gained considerable prominence in recent decades as the inevitability of change becomes increasingly apparent. Family businesses constitute a significant and influential part of the global economy. Therefore, they are pivotal in addressing the world's sustainability challenges. Despite extensive research on sustainability in corporations and public firms, there remains a dearth of comparable data concerning sustainability in privately owned family businesses. Through qualitative interviews and cross-case analyses, this thesis investigates the procurement practices within family businesses, deriving comparative insights guided by Environmental, Social, and Governance (ESG) criteria. The findings evaluate family businesses based on the ESG framework, visualising the development and integration of sustainable practices into the procurement processes. The research highlights the indirect impact of sustainability on developing competencies that can confer a competitive advantage. Additionally, it sheds light on the potential financial benefits reported by family businesses that have implemented sustainability measures. Overall, the findings contribute to the existing academic research on sustainability in businesses and family business studies.
Keywords: 330; ESG; family business; performance-based assessment; procurement; qualitative interviews; sustainability